Psychoanaliza dyskursu? Wstępne uwagi o problemach z procedurą badawczą w „postpsychoanalitycznych” naukach społecznych - Marzec, Wiktor (Śląskie Studia Polonistyczne, 2013)
The article investigates the issue of conducting empirical social research informed by psychoanalytic theories. An abundancy of contemporary theoretical perspectives – as political discourse theory – ulitises Freudian or Lacanian inspirations. However I do not question the legitimacy of psychoanalytic knowledge stemming from clinical or analysis context, I argue that using these inspirations in social research demands a prior careful consideration. Procedures and processes constituting psychoanalytic epistemology – as free association method, transference and countertransference, among others, have no direct equivalents in the context of social research or discourse analysis. Therefore, utilising psychoanalytic concepts in new context demands their reiteration, transformation and rearticulation. Some branches of psychoanalysis – as the Lacanian one – due to their theoretical structure – pose an appropriate ground for such alternations. Nevertheless, still some aspects of assumed reality escape any empirical coverage. For instance jouissance or a death drive, however elusive and ungraspable, are crucial explanatory factors for mere empirical phenomena as political identification.